Prescribing of antipsychotics in UK primary care: a cohort study. Issue 12 (18th December 2014) - Marston, Louise; Nazareth, Irwin; Petersen, Irene; Walters, Kate; Osborn, David P J
Abstract : Objective: To examine the recorded indication for antipsychotic prescriptions in UK primary care. Design: Cohort study. Setting: Primary care. Participants: Individuals prescribed antipsychotics between 2007 and 2011. Measures: The proportion of individuals prescribed antipsychotics with a diagnosis of (1) psychosis and bipolar disorder, (2) other diagnoses including depression, anxiety and dementia and (3) none of these diagnoses. Results: We identified 47 724 individuals prescribed antipsychotic agents. 13 941 received first-generation agents and 27 966 received second-generation agents. The rates of prescribing were higher in females (incidence rate ratio (IRR) 1.092 (95% CI 1.088 to 1.095), older people (80+ vs 40–49; IRR 2.234 (2.222 to 2.246)) and in those from the most deprived areas (most deprived vs least deprived IRR 3.487 (3.567 to 3.606). Of those receiving first-generation antipsychotics, less than 50% had a diagnosis of psychosis/bipolar disorder. For the second-generation agents, the numbers ranged from 4824 (36%) for quetiapine to 7094 (62%) for olanzapine. In patients without psychosis/bipolar disorder, common diagnoses included anxiety, depression, dementia, sleep and personality disorders. For example, in risperidone users, 14% had an anxiety code, 22% depression, 12% dementia, 11% sleep disorder and 4% personality disorder. The median daily doses and duration of treatment were greater in those with schizophrenia (eg, risperidone median daily dose 4 mg; IQR 2–6: median duration 1.2 years) than in those with non-psychotic/bipolar disorders such as depression or anxiety (eg, risperidone 1 mg; IQR 1–2: 0.6 years). A relatively large proportion (between 6% and 17%) of people receiving individual antipsychotics had none of the diagnoses stated above. Conclusions: In UK primary care, a large proportion of people prescribed antipsychotics have no record of psychotic or bipolar disorder. They are often older people with conditions including dementia, non-psychotic depression, anxiety and sleep disorders.